2021
DOI: 10.7759/cureus.17916
|View full text |Cite
|
Sign up to set email alerts
|

Two Different Clinical Presentations of Acute Limb Ischemia Caused by Acute Thrombotic Events in COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) is a global pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Coagulopathy is frequently found in severe cases of COVID-19 and is usually manifested as a prothrombotic state. Hyperinflammation, endotheliitis, and immobilization during illness are hypothesized to play a role. Acute limb ischemia (ALI) is one of the presentations of arterial thrombosis in COVID-19. We present two cases of middle-aged men with COVID-19 infection, who developed ALI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This process induces organ damage, release of proinflammatory cytokines, chemokines, and activation of the complement system which all lead to the hyperinflammation state known as "cytokine storm" 2 . Both microvascular dysfunction and cytokine storm are involved in thrombotic and ischemic manifestations 3 . Several studies have reported different signs of acral ischemia such as pseudo-chilblains, livedo reticularis and dry gangrene [4][5][6] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process induces organ damage, release of proinflammatory cytokines, chemokines, and activation of the complement system which all lead to the hyperinflammation state known as "cytokine storm" 2 . Both microvascular dysfunction and cytokine storm are involved in thrombotic and ischemic manifestations 3 . Several studies have reported different signs of acral ischemia such as pseudo-chilblains, livedo reticularis and dry gangrene [4][5][6] .…”
Section: Discussionmentioning
confidence: 99%
“…However, its role in arterial diseases has been less demonstrated 1,2 . Cases of acute limb ischemia and different signs of acro-ischemia in infected patients have been reported [3][4][5][6] . We report a case of dry gangrene in a patient tested positive for SARS-CoV2 without respiratory symptoms.…”
Section: Introductionmentioning
confidence: 99%